The Influence of Nickel and Tin Additives on the Microstructural and Mechanical Properties of Al-Zn-Mg-Cu Alloys - Haider T. Naeem; Kahtan S. Mohammed; Khairel R. Ahmad; Azmi Rahmat (Advances in Materials Science and Engineering)
The effects of nickel and nickel combined tin additions on mechanical properties and microstructural evolutions of aluminum-zinc-magnesium-copper alloys were investigated. Aluminum alloys containing Ni and Sn additives were homogenized at different temperatures conditions and then aged at 120°C for 24 h (T6) and retrogressed at 180°C for 30 min and then reaged at 120°C for 24 h (RRA). Comparison of the ultimate tensile strength (UTS) of as-quenched Al-Zn-Mg-Cu-Ni and Al-Zn-Mg-Cu-Ni-Sn alloys with that of similar alloys which underwent aging treatment at T6 temper showed that gains in tensile strengths by 385 MPa and 370 MPa were attained, respectively. These improvements are attributed to the precipitation hardening effects of the alloying element within the base alloy and the formation of nickel/tin-rich dispersoid compounds. These intermetallic compounds retard the grain growth, lead to grain refinement, and result in further strengthening effects. The outcomes of the retrogression and reaging processes which were carried on aluminum alloys indicate that the mechanical strength and Vickers hardness have been enhanced much better than under the aging at T6 temper.